Crystallized polyarylene ether nitrile blends with improved thermal, mechanical, dielectric properties, and processability. Issue 1 (7th May 2015) - Zheng, Penglun; Pu, Zejun; Jia, Kun; Liu, Xiaobo
Abstract : In this work, the biphenol polyarylether nitrile (BP‐PEN) films with improved processability were prepared by blending low molecular weight (LMW) with high molecular weight (HMW) of BP‐PEN. The hybrid membrane exhibited excellent thermal stability and mechanical strength. The Tid values of the films were as high as 505°C–522°C. Melting behavior studies indicated that the crystallinity of LMW BP‐PEN was higher than that of HMW, which was confirmed by the X‐ray diffraction (XRD) patterns analysis as well. Scanning electron microscope (SEM) provided additional information on morphology and phase adhesion. Additionally, the polymer crystallinity dependent on dielectric properties of blends films is reported. Most importantly, it is found that the combination of LMW and HMW BP‐PEN would be an effective method to simultaneously increase the mechanical, thermal, dielectric properties, and polymer processability. POLYM. COMPOS., 38:126–131, 2017. © 2015 Society of Plastics Engineers